Bilateral exports from Euro Zone countries to the US: Does exchange rate variability play a role? - Florian Verheyen (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2011)
The financial crisis and the debt crisis in Europe lead to pronounced swings of the / exteuro-exchange rate. The influence of this exchange rate uncertainty on exports is neither theoretically nor empirically unambiguous. Therefore, this investigation tries to find out what effect exchange rate volatility has got on exports from eleven euro zone countries to the US. Our results suggest that if exchange rate volatility exerts a significant influence on exports, it is typically negative. Furthermore, exports of SITC categories 6 and 7 seem to be affected negatively most often.
Keywords: C22; F14; F49; 330; bilateral exports; euro zone countries; exchange rate variability; ARDL bounds testing approach; Außenhandelswirtschaft; Wechselkurs; Volatilität; Exchange Rate Pass-Through; Eurozone; EU-Staaten; USA